Epidermis-Specific Metabolic Engineering of Sesquiterpene Formation in Tomato Affects the Performance of Potato Aphid Macrosiphum euphorbiae - Wang, Fumin; Park, Yong-Lak; Gutensohn, Michael (Frontiers in Plant Science, 2021)
Tomato produces a number of terpenes in their glandular trichomes that contribute to host plant resistance against pests. While glandular trichomes of cultivated tomato Solanum lycopersicum primarily accumulate a blend of monoterpenes, those of the wild tomato species Solanum habrochaites produce various sesquiterpenes. Recently we have identified two groups of sesquiterpenes in S. habrochaites accessions that negatively affect the performance and choice behavior of the potato aphid (Macrosiphum euphorbiae). Aphids are piercing-sucking herbivores that use their mouthpart to penetrate and probe plant tissues in order to ultimately access vascular tissue and ingest phloem sap. Because secondary metabolites produced in glandular trichomes can affect the initial steps of the aphid feeding behavior, introducing the formation of defensive terpenes into additional plant tissues via metabolic engineering has the potential to reduce tissue penetration by aphids and in consequence virus transmission. Here we have developed two multicistronic expression constructs based on the two sesquiterpene traits with activity towards M. euphorbiae previously identified in S. habrochaites. Both constructs are composed of a prenyl transferase and a respective S. habrochaites terpene synthase, as well as enhanced green fluorescent protein as a visible marker. All three coding sequences were linked by short nucleotide sequences encoding the foot-and-mouth disease virus 2A self-processing oligopeptide which allows their co-expression under the control of one promoter. Transient expression of both constructs under the epidermis-specific Arabidopsis CER5-promoter in tomato leaves demonstrated that formation of the two sets of defensive sesquiterpenes, β-caryophyllene/α-humulene and (-)-endo-α-bergamotene/(+)-α-santalene/(+)-endo-β-bergamotene, can be introduced into new tissues in tomato. The epidermis-specific transgene expression and terpene formation were verified by fluorescence microscopy and tissue fractionation with subsequent analysis of terpene profiles, respectively. In addition, the longevity and fecundity of M. euphorbiae feeding on these engineered tomato leaves were significantly reduced, demonstrating the efficacy of this novel aphid control strategy.